94.3k views
2 votes
Can you do this for me 3x+y=10, 2x^2+y^2=19​

User Alemv
by
5.2k points

1 Answer

2 votes

Answer:

1 , 29/11

Explanation:

3x+y = 10 ....(1)

2x² +y² = 19 ....(2)

3x+y= 10

y = 10-3x

substituting the value of y in 2nd equation

2x² + y² = 19

2x² + (10-3x)² = 19

2x² + 100 + 9x² - 60x -19 = 0

11x² - 60x +81 = 0

11x² - 33x - 27x + 81 = 0

11x( x-3) - 27(x-3) = 0

(x-3)(11x-27) = 0

x = 3, 27/11

substituting x value on first equation

x= 3 x= 27/11

y= 10-3(3) y= 10 - 81/11

= 10-9 = (110-81)/11

= 1 = 29/11

Hope it helps...

User Xhienne
by
4.7k points